HATE SPEECH AND HUMAN SOCIETY: A CRITICAL ANALYSIS - Yusuf Musa; Gabriel Asuquo (Universitas PGRI Madiun, 2021)
This paper critically analyses the concept of ‘hate speech’ and interrogates the possibilities of its impact on human society. The task before the paper is to identify the nuances and underpinning issues that surround the concept and whether it has any socio-political impact. Though the concept of hate speech is regarded as a potential social problem that can cause violence, which poses a threat to mutual co-existence in human society. Nonetheless, in the twenty-first century, the concept has become a topic of discussion globally, as such so many people try to give it a definitional vacuum which is unscientific, it is due to this that this paper uses Raphael’s three models of concept clarification as a theoretical framework to elaborate on the concept and give it a philosophical definitional vacuum. Therefore, using Raphael’s model of analysis, the paper discovers that the concept of hate speech means any form of expression online or offline, spoken or written, which includes images, posters, symbols, memes, emoji, drawings, photographs, and films, etc. which include denying or justifying mass murder, genocide, ethnic cleansing, etc. As such the paper distinguishes hate speech which only targets groups and does not necessarily trigger violent conflict, with an offensive speech that targets individuals and dangerous speech which has all the potentiality of triggering violent conflict. Therefore, from an ethical standpoint, hate speech is an improper use of human communicative prowess because it threatens human relationships, which are the essential ingredient of human society. This paper prescribes that it should be discouraged in human society.